The effect of two different fertilisers on the quality of Viola x wittrockiana Gams. seedlings - Margarita Davitkovska; Zvezda Bogevska; Boris Dorbić; Vjekoslav Tanaskovic; Romina Kabranova (My University, 2020)
This research was carried out to analyse the effect of diverse types of fertilisers on the morphological features of pansy seedlings (Viola x wittrockiana Gams.), as well as to decide on the most appropriate concentration of fertiliser in order to obtain the highest seedlings quality. Two different types of liquid fertilisers were used in this experiment - Magnicvet and Magnihortal with six treatments. Each treatment comprised 30 plants or a total of 180 plants in the experiment were used. 30 plants per treatment were measured, 50 days after planting into plastic containers. The following biometric parameters were analysed: plant height (mm), stem thickness (mm), number of branches and number of flower buds. Measurements of biometric parameters showed that the liquid mineral fertiliser Magnihortal with NPK 10-5-5 + micro elements is more appropriate as compared with the liquid mineral fertiliser Magnicvet with NPK 7-1-5 + micro elements concerning the reinforced nutrition and eventually the enhanced quality of Viola x wittrockiana Gams. seedlings. Treatment V (Magnihortal 0.3 %) showed the highest average height of seedlings, average stem thickness and average number of branches, while the treatment VI (Magnihortal 0.4 %) showed the highest average number of flower buds.
Keywords: Viola x wittrockiana Gams., seedlings, fertiliser concentration, biometric parameters